Explicit dynamics in impact simulation using a NURBS contact interface. (2nd December 2019) - Otto, Peter; De Lorenzis, Laura; Unger, Jörg F.
Summary: In this paper, the impact problem and the subsequent wave propagation are considered. For the contact discretization an intermediate non‐uniform rational B‐spline (NURBS) layer is added between the contacting finite element bodies, which allows a smooth contact formulation and efficient element‐based integration. The impact event is ill‐posed and requires a regularization to avoid propagating stress oscillations. A nonlinear mesh‐dependent penalty regularization is used, where the stiffness of the penalty regularization increases upon mesh refinement. Explicit time integration methods are well suited for wave propagation problems, but are efficient only for diagonal mass matrices. Using a spectral element discretization in combination with a NURBS contact layer the bulk part of the mass matrix is diagonal.